The Effect of Compensation and Work Environment on Motivation and its Impact on Employee Performance at the Regional Disaster Management Agency in Sidoarjo Regency - Udik Arif Muzaiyyin; Sigit Hermawan (Proceedings of The ICECRS, 2021)
The purpose of this research is to find out whether there is an effect of compensation and work environment on motivation and its impact on employee performance at the Regional Disaster Management Agency in Sidoarjo Regency. The analytical tool used in the form of a questionnaire distributed to 126 employees of the Fire Department Regional Disaster Management Agency in Sidoarjo Regency with the result that compensation has a significant effect on the motivation of the Fire Department Regional Disaster Management Agency Sidoarjo Regency; the work environment has a significant effect on the motivation of the Fire Department Regional Disaster Management Agency Sidoarjo Regency; motivation has a significant effect on the performance of the Fire Department Regional Disaster Management Agency Sidoarjo Regency; compensation does not have a direct effect on employee performance through motivation and the work environment does not have a direct effect on the performance of the Fire Department Regional Disaster Management Agency Sidoarjo Regency.